Implications of organized retailing in horticultural crops in Punjab - SINGH, SUKHPAL; SEKHON, M K; KUMAR, SUNNY; BHARDWAJ, SUMIT (The Indian Journal of Agricultural Sciences, 2021)
The economic reforms to boost foreign direct investment in retail sector initiated in India had unfavorable consequences on the ongoing traditional system. The organized retail sector, known as super markets, is likely to make a threat on the vast traditional retail sector of India. Based on primary data collected during 2016-17 from supermarket stores, unorganized retailers and consumers of Punjab, the study revealed that volume of sales, employment and profit margin of the unorganized retailers of fruits and vegetables have decreased due to the commencement of super markets. To counter the adverse impacts of supermarkets on neighborhood fruits and vegetables markets, it is suggested that pro-active government interventions in encouraging retail cooperative system and developing sufficient infrastructure for unorganized sector would help fruits and vegetable retailers for enhancing their efficiency. It would indeed be depressing to know that traditional markets which till recently were thriving have been fading away. Hence the small retailers need to be encouraged and guided to modernize not only themselves but the entire market place as well.